A Process Proposal for Implementation of Open Data in Brazilian Public Institutions - Silva, Renan de Oliveira; Júnior, Gibeon Soares de Aquino (iSys - Journal of Information Systems, 2018)
Open Data initiative has been gaining strength in recent times, with increasing participation of public institutions and governments. However, for being a new experience and because there are not many disseminated guides and processes, many difficulties emerge, causing delays in publications and other problems. Therefore, the objective of this work is to define a process that helps brazilian public institutions to open their data, guiding them during the phases and tasks of publication. For this, we carried out a systematic mapping of the literature, in order to discover strategies, best practices and difficulties that exist in the field, as well as other existing processes for study and comparison purposes.